RESPON MENOLAK DAN MENGELAK TERHADAP TINDAK TUTUR PUJIAN BERBAHASA JEPANG - Sherly Helena; Nana Rahayu; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses the refusal and evasive responses to speech acts of praise in the drama “Oh! My Boss! Koi wa bessatsu de”, “Ao Haru Ride” movie, and “Isshukan Friends” movie. The method is descriptive qualitative based on pragmatic principles. The results of the study indicate that the intention of the response to reject and evade the speech act of praise is to be polite. Based on these findings, there are two types of implicatures, namely general conversational implicatures based on Japanese culture and specific conversational implicatures based on the context of speech.Key Words: response, implicature, speech acts, praise